DEVELOPMENT OF MULTIMEDIA LEARNING PACKAGE FOR JAPANESE LANGUAGE ON THE SUBJECT OF IDIOMS FOR GIVING AND RECEIVING FOR UNDERGRADUATE JAPANESE STUDENTS - (Kanokrat Pilaphon), กนกรัตน์ ปิลาผล; (Wiwat Meesuwan), วิวัฒน์ มีสุวรรณ์ (Journal of Education and Innovation, 2018)
The purpose of this research is 1) to construct a quality Multimedia Learning package for idioms related to giving and receiving in the Japanese language for undergraduate Japanese students according to the standard of 80/80, 2) to compare the results between pre- and posttests of undergraduate Japanese students who have used the Multimedia Learning package for idioms related to giving and receiving in the Japanese language, and 3) to examine the opinions of the undergraduate students and determine the effectiveness of the package. The sample group will consist of 30 first year students in the Pibulsongkram Rajabhat University Japanese Program using purposive sampling, and the results analyzed using t-test dependent samples. The results revealed that; 1) the Multimedia Learning package for idioms related to giving and receiving in the Japanese language for undergraduate Japanese students; resulted in a higher effectiveness at 84.33/82.78, to the standard 80/80, 2) We can conclude that there is a significant statistical improvement in the scores of the students of .05, and 3) the students had a high opinion of the Multimedia package, rating the package with the mean at = 4.55, S.D. = 0.10.